Penggunaan Istilah Asing (Gairaigo) Review Makeup dalam Kanal Youtube Nanako [Neoki 1-byō]: Kajian Morfologi - Prastika, Tiara Maulina; Kadir, Puspa Mirani; Wagiati, Wagiati (KIRYOKU, 2024)
Language change is a significant impact of the evolution of the times and technological advances, facilitating global cultural communication and interaction. One example of this phenomenon is gairaigo in Japanese, which is an absorbent word from a foreign language and is very commonly used in everyday communication, especially in digital media like YouTube content. Gairaigo plays an important role in modern Japanese, especially in areas influenced by global trends such as makeup. This research aims to study the process of forming the use of gairaigo in reviewing makeup on the YouTube channel Nanako in the study of morphology. Data taken from YouTube with the title "[寝起き1秒] 春色ナチュラルだけどしっかり盛れる新作プチプラメイク [Neoki 1-byō] shunshoku nachurarudakedo shikkari moreru shinsaku puchipurameiku". The theory used in this study is the theory of Tsujimura concerning the formation of the word morphology in the Japanese language. The research method used is qualitative descriptive with data collection techniques through recording, recording, and validating data by native speakers. The analysis showed that there were 28 Gairaigo words used in the video. These words undergo three types of morphological processes: compounding, clipping, and borrowing. Examples of these are ノーズシャドウ (nozu shadō), コントゥア (kontua), and ハイライトする. (hairaito suru). The findings showed the Japanese language's adaptation to foreign words through phonetic and morphological adjustments, enriching Japanese vocabulary and reflecting complex social and cultural dynamics. A deeper understanding of these morphological processes can make a significant contribution to the linguistic and literary study of language contacts and language changes as a result of globalization.